2019
DOI: 10.1074/mcp.ra118.001288
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 1508 Plasma Samples by Capillary-Flow Data-Independent Acquisition Profiles Proteomics of Weight Loss and Maintenance

Abstract: We established a robust capillary-flow data-independent acquisition MS platform capable of measuring 31 plasma proteomes per day without the need of repeated acquisition of the same sample. We acquired 1508 samples of the DiOGenes study (multicentered, Europa-wide caloric restriction weight loss and maintenance study of overweight and obese, non-diabetic participants). This was achieved using a single analytical column. Comprehensive biological reactions to weight loss and maintenance were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
196
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(198 citation statements)
references
References 60 publications
2
196
0
Order By: Relevance
“…In this DDA method, non-resonant collision-induced dissociation mode (HCD) was chosen as unique mode of fragmentation. In sharp contrast with proteomics where a single normalized collision energy (NCE) of~30% is suitable for almost all peptides [32,33], metabolite fragmentation is strongly NCE-dependent and thus no single collision energy can be applied to fit all metabolites [17]. Optimizing applied NCE therefore represents a prerequisite to efficient DDA acquisition protocol in metabolomics.…”
Section: Implementation Of a First "Hcd-only" Dda Acquisition Protocomentioning
confidence: 99%
“…In this DDA method, non-resonant collision-induced dissociation mode (HCD) was chosen as unique mode of fragmentation. In sharp contrast with proteomics where a single normalized collision energy (NCE) of~30% is suitable for almost all peptides [32,33], metabolite fragmentation is strongly NCE-dependent and thus no single collision energy can be applied to fit all metabolites [17]. Optimizing applied NCE therefore represents a prerequisite to efficient DDA acquisition protocol in metabolomics.…”
Section: Implementation Of a First "Hcd-only" Dda Acquisition Protocomentioning
confidence: 99%
“…First introduced in the mid-2000s, 15,16 various studies up to now showed that these methods enabled an accurate, precise and comprehensive proteome quantification. [17][18][19][20][21][22][23] By fragmenting the interesting mass range in sequential, wide isolation windows (SWATH-type DIA approach 24,25 ), it was possible to identify more peptides in short gradients than could be theoretically targeted in a sequential manner using data-dependent acquisition (DDA). 26 Commonly, DIA data are analysed using a project-specific library.…”
Section: Introductionmentioning
confidence: 99%
“…Bruderer et al. recently used micro‐flow LC‐DIA‐MS to analyze 1508 plasma samples in a weight loss/obesity biomarker discovery study; they profiled 564 plasma proteins, quantifying 60 of which with SIS peptides in a 40 min gradient with CVs typically <20% . Technologies enabling larger sample cohorts to be analyzed with deeper proteome coverage, improved throughput, and high reproducibility are likely to improve the quality of putative biomarkers at an earlier stage in the discovery process.…”
Section: Role Of Emerging Technologies In Advancing Biomarker Discovementioning
confidence: 99%